Native anthropology the Japanese challenge to Western academic hegemony - Kuwayama, Takami (Japanese Society series, 2004)
The central theme of this book is the position of 'natives' in what the author calls the world system of anthropology. This book shows how anthropological knowledge is produced, disseminated, and consumed on a global scale.